Вплив роботи енергоблоків ТЕС в маневреному режимі на надійність та аварійність енергетичного обладнання - Черноусенко, Ольга Юріївна; Пешко, Віталій Анатолійович (НТУ "ХПІ", 2016)
Через недостатню кількість маневрених потужностей в ОЕС України пиловугільні блоки, спроектовані для базової роботи, залучаються до регулювання навантаження. Проаналізовано сучасний стан енергогенеруючого обладнання України, зазначено недоліки експлуатації енергоблоків по відношенню до нормативної бази. Проаналізовано вплив роботи енергоблоків ТЕС України у маневреному режимі та розраховано показники аварійності і питомі показники надійності устаткування. Зазначено, що відповідно до сучасного стану обладнання, робота у маневреному режимі є не бажаною і потребує розробки спеціальної нормативної бази, оскільки значно зношує наявні основні фонди.

Due to the insufficient amount of maneuver powers for consolidated power systems in Ukraine pulverized-coal units that were designed for the operation in the base section of the schedule of electric loads are used for the power control. The current state of energy generating equipment available in Ukraine has been analyzed, the drawbacks of the operation of power units with regard to the normative base approved by the Ministry of Power Engineering and Fuel Industry of Ukraine have been revealed. Influence of the operation of the power units of thermal power plants in Ukraine in the maneuver mode on the reliability and accident rate of power equipment has been analyzed and the accident rate indicators and the specific indicators of equipment reliability have been calculated.
Influence produced by the operation of the power units of thermal power plants in the maneuver load mode on the reliability and accident rate of power equipment
Keywords: теплові електростанції; енергоблок; об’єднана енергетична система; consolidated power system; operating time